Point-based graphics - Gross, Markus, 1963-; Pfister, Hanspeter (Amsterdam ; Boston : Morgan Kaufmann, 2007)
This book will present the latest research results in point-based computer graphics. After an overview of the key issues, affordable 3D scanning devices will be discussed and new concepts for the mathematical representation of point-sampled shapes will be presented. Then the authors will describe methods for high-performance and high-quality rendering of point models, including advanced shading, anti-aliasing, and transparency. The book will also present efficient data structures for hierarchical rendering on modern graphics processors (GPUs). In addition it will address methods for geometric processing, filtering and resampling of point models. The last part of the book will be devoted to Pointshop3D, open-source software for the design of new algorithms for point-based graphics. Both editors have worked in computer graphics for many years and have pioneered the field of point-based graphics. They have published a large number of papers in journals and conferences on this topic. They have founded the IEEE/EUROGRAPHICS annual Symposium on Point-based Graphics, which was held this year for the second time. They also taught numerous courses on the topic at international conferences, including ACM SIGGRAPH and EUROGRAPHICS. The first book on a major development in graphics by the pioneers in the field * This technique allows 3D images to be manipulated as easily as Photoshop works with 2D images * Includes CD-ROM with the open source software program Pointshop3D for experimentation with point graphics.
1. Introduction (Gross, Pfister) -- 2. A Historical Perspective (Levoy) -- 3. Acquisition -- 4. Foundations and Representations -- 5. Digital Processing -- 6. Rendering -- 7. Physics Based Animation -- 8. Selected Topics -- 9. Outlook (Gross, Pfister) -- Bibliography -- Index.
Includes bibliographical references (p. 475-514) and index.
Keywords: Computer graphics; Three-dimensional display systems; Electronic books